Pemberian Pupuk Organik Cair dari Limbah Cair Tahu Terhadap Pertumbuhan dan Hasil Kubis Bunga (Brassica oleraceae var botrytis L.) - Annida Fitria Ma'ruf; Sugiarto Sugiarto; Rika Yayu Agustini (Jurnal Ilmiah Wahana Pendidikan, 2021)
Abstract: To increase the amount of production of cauliflower can be done by developing flower cultivation in the lowlands and increasing input in the form of fertilizer. Inorganic fertilizer application of excess leads to reduced soil fertility. Organic fertilizer from tofu waste water can be used as an alternative to reduce the use of inorganic fertilizers. The aim of this study was to find out tofu waste water’s potency as organic liquid fertilizer by observing the optimal concentration for growth and yeild of cauliflower plant (Brassica oleraceae var.botrytis L.). The research method used was a single factor randomized block design (RAK), namely the concentration of POC with 6 treatments and repeated 4 times, A (control), B (POC 10%), C (POC 15%), D (POC 20%), E (25%), F (POC 30%). The results of experiment showed that the concentration of POC tofu waste water did not significantly affect the growth parameters. However, it had significant effect on the cauliflower yield parameters. The highest yields in the B treatment (POC 10%) give diameter of cauliflower (3,59 cm), the weight cauliflower with leaves (30,91 g), and weight cauliflower without leaves (25,41 g).